Konsep Metafisika Dalam Islam Sebagai Kritik Terhadap Epistemologi Barat - Afifi, Afifi Hasbunallah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2022)
Science in the modern era has separated from ethical principles and moral-spiritual (metaphysical) aspects, creating a dilemma between science and wisdom or science and moral-spiritual perfection. To understand this dilemma, it is necessary to reexamine the history of Western thought which nevertheless has a positive side in the development of science, even though in the end its epistemological foundation eliminates the universality of science itself. furthermore, it is also necessary to understand how the concept of Islamic thought in the development of science, in general, is based on an epistemology that accepts the ontological status of metaphysics as truth. For that, the most important thing to do is to accept the status of metaphysics as part of science. Because after all, the search for metaphysical reality can be considered a complement to physical science..